PENGARUH DESAIN PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN SENSITIVITAS HARGA SEBAGAI VARIABEL INETERVERNING - Ridwani, Ryan Ridho; Renwarin, Joseph M. J.; Rianto, Muhammad Richo; Rony, Zahara Tussoleha; Suroso, Sugeng (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this research is to determine the influence of product design and brand image on purchase decisions with price sensitivity as an intervening variable. This research method uses a quantitative research method, with the type and source of data being primary data from the distribution of questionnaires. The population and sample of this study are respondents who have purchased or used Ortuseight Shoes. The sampling technique used is Accidental sampling with a minimum respondent age of 15 years, resulting in 101 data samples that meet the criteria. The analysis methods used are descriptive statistical tests, outer model tests, inner model tests, and hypothesis tests. The results of this study indicate that product design affects purchasing decisions, brand image does not affect purchasing decisions, product design does not affect price sensitivity, brand image affects price sensitivity, and price sensitivity successfully influences purchasing decisions